Traumatic Narration: A Case Study of Toni Morrison’s Beloved - Abdullah Abdulateef, Huda (Journal of College of Education, 2020)
This paper examines Laurie Vickroy’s (2002) main traumatic narrative strategies of intimacy, fragmentation, the dissociation of the character’s identity, images and dialogical conceptions of witnessing. Therefore, at first, it defines trauma theory and its importance to the analysis of trauma narratives. Then, as a case study, it focuses on Toni Morrison’s Beloved (1987) in terms of its trauma narrative structure and themes that come from three different real stories. It mainly shows how Vickroy’s strategies work to uncover Beloved’s traumatic themes of mother-daughter (s) relationship, memory, community, slavery and freedom through traumatic narration of testimony and fragmented narrative structure. Eventually, this paper explains the meaning of slavery and freedom, racial violence and racial reconciliation in Beloved through its traumatic narration and structure.